THE INFLUENCE OF TAXPAYER AWARENESS AND TAX OFFICER SERVICES REGARDING INDIVIDUAL TAXPAYER COMPLIANCE KPP PRATAMA BUKITTINGGI - Jennisa Dwina Indriani; Sri Kemala; Sarmila Karina (Jurnal Ipteks Terapan : research of applied science and education, 2023)
This research aims to determine Taxpayer Awareness and Tax Officer Services regarding Mandatory Compliance Tax with a sample of 80 respondents. The data collection method related to the research problem was carried out using the questionnaire method. Data was taken in the month. The data analysis technique used in this research is the SEM (Structural Equation Modeling) analysis technique based on PLS variance . Research results from 80 respondents show that Taxpayer Awareness and Tax Officer Services at the Bukittinggi Pratama Tax Service Office in 2021 have an influence on Taxpayer Compliance.